AN ANALYSIS OF A GEOMETRY LEARNING PROCESS: THE CASE OF PROVING AREA FORMULAS - Al Jupri; Sumanang Muhtar Gozali; Dian Usdiyana (Prima: Jurnal Pendidikan Matematika, 2020)
Geometry is one of the courses in the curriculum for students of prospective mathematics teachers that can develop deductive thinking ability. The question is, how is the learning and teaching process of the geometry course implemented so as to develop this deductive thinking ability? This research, therefore, aims to investigate the learning and teaching process of a geometry course for prospective mathematics teachers. For reaching these aims, this qualitative study was conducted through observations on the learning process and the written test of a geometry course, for the case of area formulas, involving 56 students of mathematics education program. The results revealed that the learning process is implemented by emphasizing the use of the deductive approach, and from the written test we found various proof strategies in proving an area formula. We conclude that the learning and teaching process of the geometry course has influenced the development of student deductive thinking.